2D π‐conjugated metal–organic frameworks for CO2 electroreduction. Issue 1 (28th March 2022) - Yang, Deren; Wang, Xun
Abstract: Electrochemically converting CO2 molecules into valuable chemicals and fuels opens up a promising route to utilize CO2 source. To overcome the low efficiency and durability that hinder its practical applications, tremendous research efforts have been devoted to nano‐level or atomic‐level catalyst design. The advent of metal–organic frameworks (MOFs) provides novel opportunities for CO2 reduction catalysts, which may integrate the respective advantages of traditional catalysts and single‐atom catalysts. In this review, we summarize the recent advances in two‐dimensional (2D) π‐conjugated MOF catalysts and discuss their practical applications in CO2 reduction reaction (CO2 RR). First, we systematically introduce the development of electrocatalysts for CO2 RR applications. Meanwhile, various types of 2D porphyrin/phthalocyanine‐based MOFs and corresponding electrocatalytic performances arising from active‐site engineering, surface reconstruction, and thickness control are briefly overviewed. Finally, we highlight their major challenges and opportunities facing CO2 RR, and hope that this review can offer new insight into MOF catalyst design. Abstract : Two‐dimensional (2D) π‐conjugated metal–organic frameworks (MOFs), including 2D porphyrin‐based and phthalocyanine‐based MOFs, integrate the advantages of traditional catalysts and single‐atom catalysts. The ultrathin thickness, fully exposed active center, structural homogeneity, and light‐coupling capacity endow 2D π‐conjugated MOFs with great potential in CO2 reduction reaction (CO2 RR). In this review, their development and practical application in CO2 RR and photo‐coupled CO2 RR are summarized.